Unilateral Thyroid Lobe Involvement of Graves Disease. Issue 2 (6th March 2023) - Alzedaneen, Yazan; Chelsea, Moxley Meaghan; Reddy, Rashmi; Munir, Kashif M
Abstract: A 30-year-old man presented with 3-year history of Graves disease. He was initially diagnosed after he developed unilateral proptosis and was initiated on methimazole 5 mg, on which he was currently euthyroid. Visible right-sided thyromegaly and trouble swallowing developed 2 months after presentation to our practice. Biochemical evaluation revealed suppressed TSH, normal free T4 and total T3, and elevated thyroid stimulating immunoglobulin with normal thyroid receptor antibody. An ultrasound of the thyroid demonstrated left-sided small nodules with right-sided thyromegaly. A nuclear medicine uptake scan revealed significantly greater uptake in the right thyroid lobe, with overall minimal uptake in the left lobe. The need for definitive therapy that would not exacerbate orbitopathy was discussed, and the patient elected for a right-sided hemithyroidectomy. Postoperative biochemical evaluation demonstrated biochemical euthyroidism despite continued elevation in thyroid stimulating immunoglobulin and newly elevated thyroid receptor antibody while remaining off methimazole. Graves disease can rarely involve a single thyroid lobe. Given the rarity, further investigation is needed to determine the natural course of this form of Graves disease.